The diegesis of Benjamin Button: a method for comparing literature and film - Montenegro Bonilla, Joe (2013)
This article proposes a specific structuralist methodology that may help organize the analysis of the relationship between literature and cinema. Through the instance of F. Scott Fitzgerald’s short story “The Curious Case of Benjamin Button” and David Fincher’s film adaptation of it, a focus on the comparable diegetic structures of a narrative cinematic text and the literary work on which it is based is offered, along with an exploration of the semiotic codes that support their comparative textual analyses.